Intercellular communication lessons in heart failure. (23rd September 2015) - Bang, Claudia; Antoniades, Charalambos; Antonopoulos, Alexios S.; Eriksson, Ulf; Franssen, Constantijn; Hamdani, Nazha; Lehmann, Lorenz; Moessinger, Christine; Mongillo, Marco; Muhl, Lars; Speer, Thimoteus; Thum, Thomas
Abstract : Cell–cell or inter‐organ communication allows the exchange of information and messages, which is essential for the coordination of cell/organ functions and the maintenance of homeostasis. It has become evident that dynamic interactions of different cell types play a major role in the heart, in particular during the progression of heart failure, a leading cause of mortality worldwide. Heart failure is associated with compensatory structural and functional changes mostly in cardiomyocytes and cardiac fibroblasts, which finally lead to cardiomyocyte hypertrophy and fibrosis. Intercellular communication within the heart is mediated mostly via direct cell–cell interaction or the release of paracrine signalling mediators such as cytokines and chemokines. However, recent studies have focused on the exchange of genetic information via the packaging into vesicles as well as the crosstalk of lipids and other paracrine molecules within the heart and distant organs, such as kidney and adipose tissue, which might all contribute to the pathogenesis of heart failure. In this review, we discuss emerging communication networks and respective underlying mechanisms which could be involved in cardiovascular disease conditions and further emphasize promising therapeutic targets for drug development.